2019
DOI: 10.1039/c9sc03080h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light harvesting pyrene-based MOFs as efficient ROS generators

Abstract: K-region substituted pyrene-based MOFs for ROS generation upon direct visible-light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…The electron‐rich benzylamine derivatives (with ‐Me and ‐OMe) were oxidized faster than electron‐poor ones (with ‐F and ‐Cl), which suggested that the substrate electronic effect plays an important role in oxidation reactions, in line with previous reports (Figure 3 d, Figures S43–S46, and Table S3) [23c, 25d, 26] . However, in all cases, the reaction kinetics were slower than those for bare benzylamine, i.e., were also affected by substrate size [11g, 25e] . In addition, in view of the anionic nature of 1.5 wt %‐TPA, the diffusion of electron‐rich substrates into its pores should be more difficult than that of bare benzylamine, and the corresponding reaction can therefore be retarded.…”
Section: Resultssupporting
confidence: 88%
“…The electron‐rich benzylamine derivatives (with ‐Me and ‐OMe) were oxidized faster than electron‐poor ones (with ‐F and ‐Cl), which suggested that the substrate electronic effect plays an important role in oxidation reactions, in line with previous reports (Figure 3 d, Figures S43–S46, and Table S3) [23c, 25d, 26] . However, in all cases, the reaction kinetics were slower than those for bare benzylamine, i.e., were also affected by substrate size [11g, 25e] . In addition, in view of the anionic nature of 1.5 wt %‐TPA, the diffusion of electron‐rich substrates into its pores should be more difficult than that of bare benzylamine, and the corresponding reaction can therefore be retarded.…”
Section: Resultssupporting
confidence: 88%
“…employed this method to grow two visible light responsive pyrene‐based MOFs by solvothermal reactions between pyrene units (H4BPETB) and Zr6/Hf6 clusters (Figure 6). [26] …”
Section: The Ways To Prepare Pah‐based Co‐crystalsmentioning
confidence: 99%
“… The preparation of Pyrene‐based MOFs by solvothermal crystallization [26] . Reproduced by permission of Royal Society of Chemistry, Copyright 2019.…”
Section: The Ways To Prepare Pah‐based Co‐crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of highly stable MOFs based on Zr 6 clusters and Fe 3 clusters have been obtained under the guidance of HSAB principles. [23][24][25][26] It is particularly worth mentioning that Zr 6 cluster-based PCN-222 and Fe 3 cluster-based PCN-600 are rare examples of ultrastable MOFs with mesoporosity. 26,27 The metal clusters in both of the two MOFs mentioned above are linked by the same square planar, tetratopic, carboxylate ligand, tetrakis(4-carboxyphenyl)porphyrin (H 4 TCPP), which adopted a high D 4h symmetry in the two frameworks.…”
Section: Introductionmentioning
confidence: 99%